1969
DOI: 10.1017/s0007485300003394
|View full text |Cite
|
Sign up to set email alerts
|

Observations on some possible attractants of tsetse flies (Glossina morsitansWestw. andG. pallidipesAust.)

Abstract: Investigations into some possible attractants of Glossina morsitans Westw. and G. pallidipes Aust. have been described. In small cages (8x8x11 in.) under laboratory conditions, flies with painted eyes survived longer than those that were untreated, whilst removing the antennae decreased longevity. Olfactory stimuli were probably more important than vision in orientating a fly towards a static guinea-pig used as a host in a moulded mesh insert into the cage. Field observations indicated that tsetse flies were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For the entomological survey, a total of 1046 mono-pyramidal traps [ 28 ] were deployed in the 52 PAs. Three tsetse fly attractants (acetone, octenol and cow urine) were used [ 29 , 30 ]. Traps were deployed for 2 days and flies were collected twice a day at around 10:00 AM and 6:00 PM.…”
Section: Methodsmentioning
confidence: 99%
“…For the entomological survey, a total of 1046 mono-pyramidal traps [ 28 ] were deployed in the 52 PAs. Three tsetse fly attractants (acetone, octenol and cow urine) were used [ 29 , 30 ]. Traps were deployed for 2 days and flies were collected twice a day at around 10:00 AM and 6:00 PM.…”
Section: Methodsmentioning
confidence: 99%
“…Under laboratory conditions, visual and olfactory components of host-seeking behaviour are largely eliminated by the operator, although their importance has been evaluated in experimental situations (Turner, 1971;Dean et al, 19696;Brady, 1972a;Gatehouse, 1972a, b) and recently exploited in the field (Vale, 1974a, b, c).…”
Section: Nutritional Events Ingestion Of Blood-mealsmentioning
confidence: 99%
“…In Tanzania, GLASGOW et al (1958) listed various possible hosts of morsitans group flies but analyses of blood-meal squashes showed that despite the fact that warthogs and impala were most common, G. swynnertoni and G. pallidipes fed mainly on Suidae (76% and 94%, respectively). However, in the laboratory DEAN et al (1969) showed that the preference of colours decreased in the following order: ultraviolet, blue, red, white and yellow. Although impala, wildebeest, waterbuck, and particularly zebra occurred in large numbers in collection areas, they were ignored.…”
Section: Host Selection and Feeding Patternmentioning
confidence: 97%